FORUM ON ROBERT BARTLETT'S WHY CAN THE DEAD DO SUCH GREAT THINGS?: SAINTS AND WORSHIPPERS FROM THE MARTYRS TO THE REFORMATION: Introductory Remarks. Issue 4 (26th January 2017) - Sterk, Andrea
Abstract : Pondering the miraculous deeds of the early Christian saints and martyrs in his City of God, St. Augustine queried, "Why can the dead do such great things?" 1 Robert Bartlett's magisterial study takes up this question by examining the veneration of the holy dead from the age of the martyrs through the Protestant Reformation. While its center of gravity is medieval Europe, the book's long scope and comparative dimensions make it relevant to historians and scholars of religion across a broad chronological and geographic spectrum. Alongside its erudition, Bartlett's study is also remarkably accessible—full of engaging stories, good humor, and profound insight into human nature as well as social practice.